Measuring Risk Maturity Levels as a Tool for Evaluating the Effectiveness of Risk Management at PT Jasa Kepelabuhanan Petikemas Surabaya - Cahya Ardie Firmansyah; Driana Le; Nazaruddin Malik (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The level of risk maturity and to provide actionable recommendations that are aligned with the company’s efforts to develop and improve its risk management strategy and implementation. The research adopts a qualitative approach using a case study strategy. Data were collected through interviews with representatives responsible for risk management implementation, governance, and compliance functions as key risk owners within the organization. The findings indicate that the company’s risk maturity level is positioned at the good practice phase, with a score of 2.95. This result suggests that risk management has been implemented satisfactorily, while performance achievement is categorized as good. The study highlights that risk management has contributed positively to organizational performance, although further improvements remain necessary to enhance overall effectiveness. Future research is recommended to adopt quantitative or mixed-method approaches to examine the relationship between risk management maturity levels and both financial and non-financial performance indicators